A rare case of mesenchymal hamartoma of cheek masquerading as hemangioma - Viswambharan, Vivek; Narayana, M. Lakshmi; Chaithanya, N. Reddy; Kumarguru, B. N.; Sushma, Bijjam (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Hamartomas are non-neoplastic, tumor-like masses characterized by irregular overgrowth in tissues of its origin, resulting from inborn errors that occur during embryonic development and are present from birth. They may develop from any of the three germinal layers of which mesodermal-derived overgrowth is the most common. Hamartomas may be seen anywhere in the body and most often arises from lung, liver, spleen, kidney, gastrointestinal tract, and rarely in the head and neck region. A 23-year-old lady presented with a painless left cheek swelling for three months. On clinical examination, she had a single, firm and ill-defined swelling of size 2×1cms in left cheek. Ultrasound examination showed an ill-defined hypoechoic lesion measuring 2.1×0.8 cms in the intramuscular compartment of left cheek with few cystic areas. On colour doppler there was minimal peripheral vascularity and flow signal suggesting capillary hemangioma. In view of the tumor’s vascularity, Fine needle aspiration cytology wasn’t performed and she was treated conservatively on oral propranolol. But since no significant response was noted, excision biopsy was done under general anesthesia. The histopathology features were consistent with mesenchymal hamartoma. Post-operative period was uneventful, and she was in regular follow up with no recurrence.